Paternal response to novel predator exposure correlates with transgenerational response in offspring of threespined stickleback - Michaela M. Rogers; Jennifer K. Hellmann (Royal Society Open Science)
Parental experiences can alter offspring phenotypes via transgenerational plasticity (TGP), which may prime offspring to adaptively respond to novel stressors, including novel predators. However, we know little about the types of sensory cues (e.g. visual, olfactory) that parents use to recognize novel predators and the consequences for offspring. Individuals may respond to novel cues if they mimic historical cues or they may need multiple sensory cues to recognize and respond to novel stimuli. We exposed threespined stickleback (Gasterosteus aculeatus) males to a full factorial of visual and olfactory cues of a novel trout predator prior to fertilization and tested offspring for antipredator behaviour and survival against a live predator. Fathers exposed to visual cues oriented more to and spent time closer to the novel predator post-exposure on the first day. Paternal response to visual cues was echoed in their offspring: offspring of fathers exposed to visual cues were caught faster by a live predator, suggesting that multiple cues are not needed to induce a transgenerational effect. While visual cues elicited responses both within- and transgenerationally, they do not seem to result in adaptive priming in offspring, suggesting the possibility of maladaptive TGP in response to novel cues of predation risk.